Trends in tuberculosis – is a different problem emerging? - Tejaswini Olambe; Pooja Shah; Sae Pol; Vaishali Gaikwad; Sujata Dharmshale; Rajesh Karyakarte (Asian Journal of Medical Sciences, 2024)
Background: Tuberculosis (TB), as a communicable disease, is an ongoing global epidemic that accounts for a high burden of global mortality and morbidity. Drug-resistant TB strains are one of the hurdles in controlling TB problem. TB is the most common opportunistic infection in people living with human immunodeficiency viruses (PLHIV). To accelerate progress toward the goal of ending TB by 2035, it is imperative to outline the incidence and mortality trends of TB in India. Aims and Objectives: This study aims to provide deep insights into the recent trends of TB incidence and mortality in India from 2018 to 2023. Materials and Methods: This is a cross-sectional type of observational study done, over a period of 6 years from 2018 to 2023. It included 21,223 suspected samples tested for TB and rifampicin (rif) resistance with GeneXpert CBNAAT (cepheid) for infection of Mycobacterium tuberculosis (MTB). Results: Out of total 21,223 samples tested, 17.97% of samples were positive for MTB. From the year 2018 to 2023, 9.5% decline was seen in overall TB cases. However, the diagnosis of rif resistance is in similar range for all the study years. New patients show slight decline, but previous patients show higher rif resistance. There is decreased TB incidence in PLHIV. Conclusion: Overall, the incidence of TB has decreased in the past 6 years. The acquired drug resistance was seen in 32.6% cases. The study found an overall decrease in the incidence of TB in PLHIV.